Weekly anal Dilatation after Anoplasty in Low Variety Anorectal Malformations - A Cross Sectional Study - Muhammad Amir Hanif Khan, Muhammad Riaz-ul-Haq, Iram Uzma Khalid, Shahnab Ahmad, Mahreen Zahra Ahmad, M. Kashif (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Low variety anorectal malformations (ARM) include almost one half of all anorectal malformations. Most of them undergo single stage anoplasty in neonatal age as an emergency procedure. Anal Dilatation is started after 10-14 days of surgery as a general protocol. Aim of our study was to measure the outcome of weekly dilatation instead of daily dilatation plan in low variety ARM patients undergoing anoplasty in terms of complications. Materials and Methods: After Ethical considerations, a prospective cross sectional study was carried out from April 2020 to March 2022 in the Department of Pediatric Surgery, The Children Hospital and the Institute of Child Health, Multan. 34 patients of low variety of ARM were included in the study. Anoplasty was done on Hager dilator no. 10. After two weeks of surgery, the patients were called for weekly follow up and dilatation. The dilatation was performed as an outpatient procedure for three months and then monthly for three months. After data collection on a pre-designed performa, statistical analysis was done using SPSS version 20. Results: Constipation was seen in 10 (29.4%) patients, followed by anal stenosis in 6 (17.6%) and wound dehiscence in 3 (8.8%) patients. Most of the patients responded to oral laxatives and intravenous antibiotics. 3 (8.8%) patients needed redo anoplasty. Overall, 26 patients (76.5%) did well on weekly dilatation program, while in 8 (23.5%) weekly dilatation program had to be converted to daily dilatation program. Conclusion: Weekly calibration by surgeons has acceptable outcomes. It is kinder and gentle to patients and lessens excessive physical and psychological trauma and morbidity to patients. The weekly dilatation plan will benefit patients not only financially but it will also lessen the psychological and physical trauma to the patients and their caregivers. Key words: anorectal malformations, low variety, anal dilatation.